Ameloblastic fibrosarcoma of the upper jaw: Report of a rare case with long-term follow-up - Maryam Khalili; Pouyan Amini Shakib (Wolters Kluwer Medknow Publications, 2013)
Ameloblastic fibrosarcoma (AFS) is a rare malignant mixed odontogenic tumor which is usually considered as the malignant counterpart of ameloblastic fibroma. Only mesenchymal component represents sarcomatous alterations and ameloblast-like epithelial nest remains bland in AFS. Here, we report a case of AFS in a 26-year-old man in the maxilla, which was regarded as an uncommon location for this tumor. After 2 years follow up, no evidence of recurrence was noted. We also emphasize on comprehensive clinical, radiographic, and histopathologic evaluation of such patients rather than immunohistochemical staining to make an accurate diagnosis.